Aurora borealis and the arctic climate change: is there any relation? - Kotrotsiou, El.; Anastassopoulos, St. (Open Schools Journal for Open Science, 2020)
In our study we tested the hypothesis that one of the causes of climate change could also be the recently observed solar hyperactivity, since it differentiates the way clouds are formed. We analyzed, from specific databases, the speed (km/s) and the proton density (p/cm3) of the solar storms in the atmosphere along with the ambient temperature and the ice extent in the arctic over the last eleven (11) years. Our study indicates indeed an explicit increase of the speed and the density of the solar wind. A not so definite analogy between the temperature’s increase and the limitation of the arctic ice extent is also noticed. Yet, the period studied is short to establish a clear relation between the rise of temperature with the enhanced solar activity. A further investigation should be followed, documenting values of more solar activity and climate change parameters during longer periods of recent time to make safe conclusions.